Simulation of Compressible Two-Phase Flows Using a Void Ratio Transport Equation (Communications in Computational Physics, 2018)
A compressible and multiphase flows solver has been developed for thestudy of liquid/gas flows involving shock waves and strong expansion waves leadingto cavitation. This solver has a structure similar to those of the one-fluid Euler solvers,differing from them by the presence of a void ratio transport-equation. The modeland the system of equations to be simulated are presented. Results are displayed forshock and expansion tube problems, shock-bubble interaction and underwater explosion.Close agreement with reference solutions, obtained from explicit finite volumeapproaches, is demonstrated. Different numerical methods are additionally displayedto provide comparable and improved computational efficiency to the model and thesystem of equations. The overall procedure is therefore very well suited for use ingeneral two-phase fluid flow simulations.
Keywords: Compressible two-phase flows; cavitation; homogeneous model; shock and expansion waves; inviscid simulation.